2015
DOI: 10.1021/am506374t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Magnetic Bead Surface Functionalities for RNA Extraction and Detection

Abstract: Magnetic beads are convenient for extracting nucleic acid biomarkers from biological samples prior to molecular detection. These beads are available with a variety of surface functionalities designed to capture particular subsets of RNA. We hypothesized that bead surface functionality affects binding kinetics, processing simplicity, and compatibility with molecular detection strategies. In this report, three magnetic bead surface chemistries designed to bind nucleic acids, silica, oligo (dT), and a specific ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…In addition, it can be readily applied to study RNA metabolism, such as RNA capping, RNA decapping and RNA decay. Notably, when combined with transcript-specific purification technology (76), it enables quantification of cap structures in specific transcripts and thus studies of transcript-specific capping and decapping, and gene-specific regulation. Finally, it permits investigations into the roles that cap-binding proteins, such as eIF4E and CBC, may play in the control of gene expression (77).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be readily applied to study RNA metabolism, such as RNA capping, RNA decapping and RNA decay. Notably, when combined with transcript-specific purification technology (76), it enables quantification of cap structures in specific transcripts and thus studies of transcript-specific capping and decapping, and gene-specific regulation. Finally, it permits investigations into the roles that cap-binding proteins, such as eIF4E and CBC, may play in the control of gene expression (77).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that chemical conditions can also be changed to preserve proteins in their native state for further proteomic analyses [ 37 ]. However, the abovementioned 3′ skew bias has been faced in different approaches, like the cDNA transcription using SMARTer [ 28 ] or the additional mRNA enrichment by its 5′cap [ 38 , 39 ]. The latter procedure also deals with the intricate capturing of mRNAs with short poly-A tails since its length might be influenced in the course of translational control [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first magnetic particle used for extraction consisted of an iron-oxide core covered by functional carboxylic group, which then binds DNA or RNA [81]. Since then, many modifications have been made using different surface functional group, such as sulphate, amino, and hydroxyl groups [82]. Besides these functional groups, preactivated magnetic beads with different functional groups are available such as tosyl or epoxy groups [78, 83].…”
Section: Devices Used In Extraction Methodsmentioning
confidence: 99%